The epidemiology and direct healthcare costs of aseptic nonunions in Germany – a descriptive report. Issue 8 (17th August 2022) - Walter, Nike; Hierl, Katja; Brochhausen, Christoph; Alt, Volker; Rupp, Markus
Abstract : Aims: This observational cross-sectional study aimed to answer the following questions: 1) how has nonunion incidence developed from 2009 to 2019 in a nationwide cohort; 2) what is the age and sex distribution of nonunions for distinct anatomical nonunion localizations; and 3) how high were the costs for surgical nonunion treatment in a level 1 trauma centre in Germany? Methods: Data consisting of annual International Classification of Diseases (ICD)-10 diagnosis codes from German medical institutions from 2009 to 2019, provided by the Federal Statistical Office of Germany (Destatis), were analyzed. Nonunion incidence was calculated for anatomical localization, sex, and age groups. Incidence rate ratios (IRRs) were determined and compared with a two-sample z-test. Diagnosis-related group (DRG)-reimbursement and length of hospital stay were retrospectively retrieved for each anatomical localization, considering 210 patients. Results: In 2019, a total of 11, 840 nonunion cases (17.4/100, 000 inhabitants) were treated. In comparison to 2018, the incidence of nonunion increased by 3% (IRR 1.03, 95% confidence interval (CI) 0.53 to 1.99, p = 0.935). The incidence was higher for male cases (IRR female/male: 0.79, 95% CI 0.76 to 0.82, p = 0.484). Most nonunions occurred at the pelvic and hip region (3.6/100, 000 inhabitants, 95% CI 3.5 to 3.8), followed by the ankle and foot as well as the hand (2.9/100, 000 inhabitants each). Mean estimated DRG reimbursement for in-hospital treatment of nonunions was highest for nonunions at the pelvic and hip region (€8, 319 (SD 2, 410), p < 0.001). Conclusion: Despite attempts to improve fracture treatment in recent years, nonunions remain a problem for orthopaedic and trauma surgery, with a stable incidence throughout the last decade. Cite this article: Bone Joint Res  2022;11(8):541–547.